Occurrence, sources and human exposure assessment of SCCPs in indoor dust of northeast China. (June 2017) - Liu, Li-Hua; Ma, Wan-Li; Liu, Li-Yan; Huo, Chun-Yan; Li, Wen-Long; Gao, Chong-Jing; Li, Hai-Ling; Li, Yi-Fan; Chan, Hing Man
Abstract: Short-chain chlorinated paraffins (SCCPs) are widely used chemicals in household products and might cause adverse human health effects. However, limited information is available on the occurrence of SCCPs in indoor environments and their exposure risks on humans. In this study the concentrations, profiles and human exposure of SCCPs in indoor dust from five different indoor environments, including commercial stores, residential apartments, dormitories, offices and laboratories were characterized. The SCCPs levels ranged from 10.1 to 173.0 μg/g, with the median and mean concentration of 47.2 and 53.6 μg/g, respectively. No significant difference was found on concentrations among the five microenvironments. The most abundant compounds in indoor dust samples were homologues of C13 group, Cl7 group and N20 (N is the total number of C and Cl) group. In the five microenvironments, commercial stores were more frequently exposed to shorter carbon chained and higher chlorinated homologues. Three potential sources for SCCPs were identified by the multiple linear regression of factor score model and correspondence analysis. The major sources of SCCPs in indoor dust were technical mixtures of CP–42 (42% chlorine, w/w) and CP–52 b (52% chlorine, w/w). The total daily exposure doses and hazard quotients (HQ) were calculated by the human exposure models, and they were all below the reference doses and threshold values, respectively. Monte Carlo simulation was applied to predict the human exposure risk of SCCPs. Infants and toddlers were at risk of SCCPs based on predicted HQ values, which were exceeded the threshold for neoplastic effects in the worst case. Our results on the occurrences, sources and human exposures of SCCPs will be useful to provide a better understanding of SCCPs behaviors in indoor environment in China, and to support environmental risk evaluation and regulation of SCCPs in the world. Graphical abstract: Highlights: The most abundant compounds in indoor dust samples were homologues of C13 group, Cl7 group and N20 group. In the five microenvironments, commercial stores were more frequently exposed to shorter carbon chained and higher chlorinated homologues compared to other indoor environments. Three potential sources for SCCPs were identified by the FA-MLR model and correspondence analysis. Infants and toddlers are at risk of SCCPs based on predicted HQ values which were exceeded the threshold for neoplastic effects in the worst cases. Abstract : Occurrence, sources, and human exposure of short-chain chlorinated paraffins in indoor dust from five different indoor environments were characterized.